Taxonomy and ethnobotany of Acmella (Asteraceae) in Thailand (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Panyadee P, Inta A. 2022. Taxonomy and ethnobotany of Acmella (Asteraceae) in Thailand. Biodiversitas 23: 2177-2183. Thai toothache plant is an ethno-species, referred to as any species in the genus Acmella of the aster family (Asteraceae). The plants are used commonly in Thailand as vegetables and medicine. However, in earlier phytochemistry and ethnobotanical studies, missed scientific names: Acmella olearcea and Spilanthes acmella, were applied to these species. In this study, we have clarified the identity of these ethno-species and related species in the genus Acmella. There were six species of Acmella in Thailand, including two native species and four introduced species. The keys and brief description of these species are provided. In ethnobotanical studies, A. oleracea and S. acmella were mentioned as nearly 80% of total use records. These names could be referred to A. paniculata which is one of the native species and most widely distributed. Although there were a reasonable amount of studies on the Thai toothache plant, more comparative studies for their bioactivities are still needed according to the taxonomical confusion of their names.